PERFORMANCE EVALUATION OF DOHUK WATER TREATMENT PLANT - HASSAN, JWAN N. (Journal of Duhok University, 2017)
Dohuk water treatment plant supplies drinking water to duhok city with 11000 m3/hr capacity and serving around 650000 capita. In this study, the plant performance evaluated through studying the turbidity efficiency removal of each unit in the plant as well as the overall removal efficiency. The data were collected from daily laboratory water quality analysis reports covering the period from 1-10-2010 through 31-10-2013 with total number of samples 825 (excluding the days were the plant was out of duty or samples did not taken). Statistical Analysis techniques shows that the water treatment plant performance was acceptable and about (97.82 %) of the supplied water match the Iraqi drinking water standards. All units are efficient except the pre-sedimentation tank which is insufficient.